Factors Affecting the Electricity Consumption and Productivity of the Lead Acid Battery Formation Process. The Case of a Battery Plant in Colombia - Balbis Morejon, Milen; Cabello Eras, Juan Jose; Sagastume Gutierrez, Alexis; Sousa Santos, Vladimir; Perez Gomez, Yabiel; Rueda Bayona, Juan Gabriel (International Journal of Energy Economics and Policy, 2019)
This study identifies the main factors affecting the electricity efficiency and productivity of the lead acid battery formation process. A representative sample of 12,286 battery formation processes, developed between June 2014 and June 2015, were used in a statistic analysis. As a result, an energy performance indicator was developed to assess the electricity consumption of battery formation. Given that there are several formation circuits in the formation area, an energy performance indicator was developed for each circuit. The influence of the operational practices, operational teams, workings shift starting time and technical condition of the circuits were analyzed. The influence of the operational practices and the technical conditions of the formation circuits were identified as the main factors affecting the productivity and the electricity consumption. These factors cause a time waste, affecting productivity between 2 and 5%, and increasing the electricity consumption. As a result it is recommended to improve maintenance and operational practices towards higher productivity and electricity efficiency. Keywords: Energy efficiency, productivity, training process, lead-acid batteries. JEL Classifications: K32, L94 DOI: https://doi.org/10.32479/ijeep.8021